Martensitic steel for high-pressure hydrogen component, high-pressure hydrogen component therewith and producing method thereof

A martensitic stainless steel with a specific chemical composition and heat treatment process addresses the challenges of high Ni content and inferior properties in existing high-pressure hydrogen components, achieving excellent toughness, corrosion resistance, and cost-effectiveness.

JP2025054905APending Publication Date: 2025-04-08AICHI STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023164124
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing high-pressure hydrogen components face challenges with high Ni content in austenitic stainless steels, leading to increased cost and weight, as well as inferior corrosion resistance and low-temperature toughness in martensitic stainless steels.

Method used

A martensitic stainless steel with a chemical composition of C: 0.01-0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00-5.70%, Cr: 17.00-20.50%, Mo: 0.20-2.00%, and optional elements Ca and B, is developed. This steel is processed through quenching and tempering heat treatments to achieve optimal properties.

Benefits of technology

The resulting martensitic stainless steel exhibits excellent low-temperature toughness, corrosion resistance, and stress-corrosion cracking resistance, while reducing Ni content to lower costs and weight, making it suitable for harsh high-pressure hydrogen environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054905000001
    Figure 2025054905000001
  • Figure 2025054905000002
    Figure 2025054905000002
  • Figure 2025054905000003
    Figure 2025054905000003
Patent Text Reader

Abstract

To provide a martensitic stainless steel for high-pressure hydrogen components almost free from strength decrease under high pressure hydrogen environment, excellent in low temperature toughness, extremely excellent also in corrosion resistance, and capable of realizing resource saving compared with a conventional stainless steel material for high-pressure hydrogen components, and a high-pressure hydrogen component therewith.SOLUTION: A martensitic stainless steel for high-pressure hydrogen components has a chemical composition that includes C: 0.01-0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00-5.70%, Cr: 17.00-20.50%, Mo: 0.20-2.00%, and, as optional elements, Ca: 0.0005-0.0030%, and B: 0.0005-0.0050%, satisfying the equation 3.0>Ni-0.8Cr+11.36>0 (where the element symbols in equation 1 represent the content percentage (%) of each element), with the balance consisting of Fe and inevitable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a martensitic stainless steel for high-pressure hydrogen components, a high-pressure hydrogen component using the same, and a method for manufacturing the same. [Background technology]

[0002] Stainless steel materials with austenitic structure (austenitic stainless steels) such as SUS316, SUS316L, and SUS305 are generally used for parts that come into contact with high-pressure hydrogen gas in fuel cell vehicles and hydrogen stations (hereinafter referred to as "high-pressure hydrogen parts") The strength of these steels is not reduced or only slightly in a high-pressure hydrogen environment, making it easy to design equipment. In addition, because they have excellent corrosion resistance, parts made of these steels do not need to be painted, and regular inspections when the parts are in use are also easy.

[0003] However, these austenitic stainless steels contain a large amount of Ni, which not only makes them expensive, but also causes problems such as low 0.2% yield strength in a solution heat treated state, which makes high-pressure hydrogen parts such as pipe joints and valves thick, large, and heavy. To solve this problem, they are sometimes cold worked after solution heat treatment. However, to ensure the desired strength, it is necessary to impart strain according to the desired strength value, but because the strain distribution inside the part after cold working is complex, it is not easy to freely adjust the strain value by cold working and ensure the desired strength.

[0004] On the other hand, general-purpose martensitic stainless steels such as SUS420J2 and SUS410 do not contain a large amount of Ni, so they are cheaper than austenitic stainless steels, and the tempered hardness can be adjusted by optimizing the heat treatment conditions, so they have the advantage of being easy to adjust in terms of strength. However, general-purpose martensitic stainless steels have inferior corrosion resistance compared to austenitic stainless steels, and it is difficult to use them with the steel surface exposed in high-pressure hydrogen parts where relatively excellent corrosion resistance is required. In addition, general-purpose martensitic stainless steels have low toughness at low temperatures, so there is a problem that they are difficult to apply to high-pressure hydrogen parts that are exposed to low temperatures, such as when filling with hydrogen.

[0005] Patent Document 1 proposes the use of martensitic low-alloy steel with relatively small amounts of Ni and Mo for high-pressure hydrogen components. However, the low-alloy steel proposed therein still needs to be improved in terms of corrosion resistance and other aspects, and is not necessarily optimal for high-pressure hydrogen components.

[0006] In order to solve the above problems, a new martensitic stainless steel for high-pressure hydrogen use that has improved corrosion resistance and toughness compared to conventional general-purpose martensitic stainless steels has been developed, and a patent application has been filed (PCT / JP2023 / 009928).

[0007] The martensitic stainless steel for high-pressure hydrogen components in this prior patent application contains approximately 5% Ni, but the Ni content is lower than that of conventional austenitic stainless steels, making it possible to reduce costs. In addition, unlike austenitic stainless steels, it has the excellent features of being able to adjust its strength through heat treatment, and of being able to ensure that its properties, corrosion resistance, and low-temperature toughness in high-pressure hydrogen environments are at levels that do not cause problems when used as high-pressure hydrogen components. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-188716 A Summary of the Invention [Problem to be solved by the invention]

[0009] The proposals of the above-mentioned prior patent applications make it possible to obtain martensitic stainless steels that have improved corrosion resistance and toughness compared to conventional martensitic stainless steels and can be used in high-pressure hydrogen environments. However, some applications of high-pressure hydrogen parts may require application to parts that are expected to be used in more severe corrosive environments where adhesion of sea salt particles is unavoidable, such as high-pressure hydrogen parts used in ships using fuel cells and high-pressure hydrogen piping parts in cold regions exposed to salt mist containing snow-melting agents. In such cases, it is necessary to develop stainless steels for high-pressure hydrogen that can further improve corrosion resistance compared to the stainless steels of the prior patent applications. In addition, when used in these applications, it is necessary to consider use in more severe corrosive environments under stress loading. In such cases, there is a concern about stress corrosion cracking, so there has been a demand for the development of steels that are excellent in both corrosion resistance and stress corrosion cracking resistance.

[0010] In view of the above background, the present invention seeks to overcome the technical challenges in reducing the cost of high-pressure hydrogen parts, and provides a martensitic stainless steel for high-pressure hydrogen parts which suffers almost no decrease in strength in a high-pressure hydrogen environment, has excellent low-temperature toughness, is extremely corrosion-resistant, achieves resource savings compared to conventional stainless steel materials for high-pressure hydrogen parts, has excellent stress corrosion cracking resistance, and can be used safely even in severe corrosive environments under high stress, as well as a high-pressure hydrogen part using the same and a method for manufacturing the same. [Means for solving the problem]

[0011] One aspect of the present invention is, in mass %, C: 0.01-0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00~5.70%, Cr: 17.00~20.50%, Mo: 0.20-2.00%, Optional elements: Ca: 0.0005-0.0030%, As an optional element, B: 0.0005 to 0.0050% is included, The following formula 1 is satisfied: Formula 1:3.0>Ni-0.8Cr+11.36>0, (Note that the element symbols in formula 1 represent the content (%) of each element.) The martensitic stainless steel for high-pressure hydrogen components has a chemical composition consisting of Fe and unavoidable impurities as the balance.

[0012] Another aspect of the present invention is a high-pressure hydrogen part made of the above-mentioned martensitic stainless steel for high-pressure hydrogen parts.

[0013] Yet another aspect of the present invention is a method for producing a high-pressure hydrogen part using the martensitic stainless steel for high-pressure hydrogen parts, comprising the steps of: A part made of a steel material having the above-mentioned chemical composition is subjected to a quenching heat treatment in which the part is held at a temperature of 900°C to 1020°C and then rapidly cooled, Thereafter, the part is subjected to a tempering heat treatment in which the part is held at a temperature of 640°C to 770°C and then rapidly cooled. This is the manufacturing method for high-pressure hydrogen parts. Effect of the Invention

[0014] The martensitic stainless steel for high-pressure hydrogen parts and the high-pressure hydrogen parts have a lower Ni content than conventional austenitic stainless steels to conserve resources, and have the specific chemical composition adjusted to satisfy formula 1, so that when produced under appropriate conditions, there is almost no loss in strength even in a high-pressure hydrogen environment, and the martensitic stainless steel and the high-pressure hydrogen parts have excellent low-temperature toughness and corrosion resistance. Furthermore, by adding an appropriate amount of Mo, the degree of improvement in corrosion resistance can be significantly increased, making it possible to expand the range of applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] First, the reasons for limiting the chemical composition of the martensitic stainless steel for high-pressure hydrogen parts (hereinafter referred to as "the stainless steel of the present application") will be explained.

[0016] C: 0.01-0.05%, C (carbon) combines with Cr during tempering heat treatment and precipitates as carbide, thereby lowering the Cr concentration dissolved in the steel and deteriorating the corrosion resistance, and also lowering the mobile dislocation density of fresh martensite, so it is desirable for the C concentration to be low. In addition, C has the effect of increasing the hardness of the martensite structure during quenching, and is prone to cracking in the as-quenched state, and in order to avoid cracking, the handling of the steel material during casting, hot rolling, and hot forging becomes complicated, which is a factor in increasing costs, so it is desirable for the C concentration to be low from this point of view as well. Therefore, the C content is limited to 0.05% or less. From the viewpoint of corrosion resistance, the C content is preferably 0.04% or less.

[0017] On the other hand, if the C concentration is too low and the chemical composition is on the austenite stable side (martensite phase rich side), the steel will contain many crystals with low mobile dislocation density, and the steel will be easily bent due to room temperature creep deformation caused by its own weight after rolling or heat treatment, which increases the effort required for straightening and makes it difficult to produce the steel. Therefore, the lower limit of the C content is set at 0.01%.

[0018] Si: 0.70% or less, Silicon (Si) is a necessary component for reduction refining in the smelting of stainless steel. However, since Si is a ferrite stabilizing element, if added in excess, a large amount of ferrite crystals, which are highly susceptible to hydrogen embrittlement, will form in the metal structure, so the upper limit is set to 0.70%. The Si content is preferably 0.60% or less. There is no particular lower limit for the Si content, but since it is difficult to avoid contamination from the slag components used during refining, it is usually set to 0.10% or more.

[0019] Mn: 1.10% or less, Mn (manganese) is a necessary component for refining together with Si in the smelting of stainless steel. In addition, when smelting from scrap, Mn is an unavoidable element, and in this case, Mn is usually contained at 0.30% or more. However, excessive addition of Mn easily forms MnS, which reduces corrosion resistance, so the upper limit of Mn content is set to 1.10%. The Mn content is preferably 1.00% or less, more preferably 0.80% or less.

[0020] P: 0.040% or less, P (phosphorus) is an element that is inevitably mixed in during the refining process of stainless steel made from scrap collected from the market. Excessive P content makes the steel more susceptible to cracking during solidification, so the upper limit of the P content is set to 0.040%. It is preferable to set the upper limit of the P content to 0.035%.

[0021] S: 0.030% or less, S (sulfur) combines with Mn in the steel to form MnS, which deteriorates corrosion resistance and hot workability, so the upper limit is set to 0.030%. In addition, S segregates at the grain boundaries between austenite and ferrite during hot working, impairing hot workability, so the upper limit is preferably set to 0.010%. More preferably, it is set to 0.005% or less. There is no particular lower limit for the S content, but since this is a low-C steel type and it is difficult to extend the reduction refining time, it is usually set to 0.0005% or more.

[0022] Ni: 4.00~5.70%, Ni (nickel) is a strong austenite stabilizing element, has a high effect of suppressing the formation of ferrite crystals, and is an important element that also improves corrosion resistance, and is contained in an amount of 4.00% or more in order to obtain these effects. Preferably, Ni is contained in an amount of 4.60% or more. On the other hand, Ni is an expensive element, and when Ni is contained in a large amount, the Mf point becomes below room temperature and a large amount of residual austenite is generated, which causes inconveniences such as a decrease in yield strength and a decrease in corrosion resistance due to microsegregation of components. In addition, the residual austenite may generate processing-induced martensite during plastic deformation at low temperatures, which is harmful to maintaining strength in a high-pressure hydrogen environment. Therefore, the upper limit of the Ni content is set to 5.70%. Preferably, the upper limit of the Ni content is set to 5.10%.

[0023] Cr: 17.00~20.50%, Cr (chromium) is an important element that contributes to the corrosion resistance of stainless steel, and in order to obtain good corrosion resistance, the lower limit is set to 17.00%. It is preferable that the lower limit of the Cr content is set to 17.50%. On the other hand, if the Cr concentration is high, the amount of ferrite increases, making it difficult to maintain tensile strength in a low-temperature, high-pressure hydrogen environment, so the upper limit is set to 20.50%. It is preferable that the upper limit of the Cr content is set to 19.50%.

[0024] Mo: 0.20-2.00%, Mo (molybdenum) is an element that improves the corrosion resistance of stainless steel, and its addition can significantly improve the degree of corrosion resistance. To achieve this effect, the content is set to 0.20% or more. On the other hand, a high Mo content leads to problems of high costs and resource saving, so the upper limit is set to 2.00%. In particular, by improving the corrosion resistance of the martensitic stainless steel of the present application, it is possible to use the martensitic stainless steel in a more severe corrosive environment, thereby solving the problems of both corrosion resistance and stress corrosion cracking resistance. From these viewpoints, the Mo content is preferably 0.50 to 1.50%, and more preferably 0.80 to 1.20%.

[0025] Optional elements: Ca: 0.0005-0.0030%, The addition of a small amount of Ca (calcium) bonds with S in steel to form CaS, which reduces the amount of S dissolved in the steel and improves hot workability. In the case of the stainless steel of the present application, the addition of Ca reduces the amount of dissolved S, suppressing S segregation to grain boundaries, particularly in hot working at temperatures exceeding 1150°C, and significantly improves the ductility of the steel during hot working. Note that Ca is not necessarily a necessary element when hot working at 1150°C or lower.

[0026] To obtain the effect of improving hot workability by adding Ca, it is preferable to add 0.0005% or more. On the other hand, excessive addition of Ca increases oxide-based inclusions in the steel, so the upper limit is preferably set to 0.0030%. When adding Ca, it is preferable to add it simultaneously with B, which also has the effect of suppressing S segregation to grain boundaries.

[0027] Optional elements: B: 0.0005-0.0050%; The addition of a small amount of B (boron) has the effect of suppressing S segregation to grain boundaries and improving hot workability. In the case of the stainless steel of the present application, the addition of B reduces the amount of dissolved S, suppressing S segregation to grain boundaries, particularly in hot working at temperatures exceeding 1150°C, and significantly improves the ductility of the steel material during hot working. However, B is not necessarily an essential element when hot working at 1150°C or lower.

[0028] As mentioned above, the addition of B is not essential, but if it is desired to obtain the effect of improving hot workability by its addition, it is necessary to add at least 0.0005% or more, and preferably 0.0020% or more. On the other hand, excessive addition of B causes an increase in unintended inclusions such as borides, so the upper limit should be set at 0.0050%, and preferably 0.0040%. When adding B, it is preferable to add it simultaneously with Ca, which also has the effect of suppressing S segregation to grain boundaries.

[0029] Formula 1:3.0>Ni-0.8Cr+11.36>0, (Note that the element symbols in formula 1 represent the content (%) of each element.)

[0030] Formula 1 specifies the range within which a suitable metal structure can be obtained by restricting the amount of ferrite structure while making the martensite structure the main phase in the quenched and tempered heat treatment state.

[0031] Although formula 1 is simple, by setting the component range with the lower limit exceeding 0, it is possible to control the metal structure so that the amount of ferrite structure is not excessive (for example, 40% or less in area ratio), and to make the mechanical properties (tensile strength, 0.2% yield strength) in a low-temperature, 90 MPa, high-pressure hydrogen environment at -45°C almost equivalent to those in air.

[0032] In iron with a BCC crystal structure, when plastic deformation occurs in a hydrogen-containing state such as in a high-pressure hydrogen environment, the concentration of vacancies in the crystal increases as dislocations move with the plastic deformation. This is widely known as the hydrogen-assisted vacancy theory. Based on the fact that the concentration of vacancies in steel increases due to plastic deformation in a hydrogen environment, it is inferred that as the increase in vacancies progresses due to the influence of hydrogen during plastic deformation, the diffusion of iron atoms becomes easier, which promotes the slip deformation of the crystal, and microcracks occur before cross slip occurs, causing local stress concentration, leading to a decrease in the ductility of steel in a hydrogen environment.

[0033] Therefore, in order to increase the elongation of iron with a BCC crystal structure in a hydrogen-containing state such as a high-pressure hydrogen environment and maintain the same tensile strength as in air, it is necessary to make as many slip planes as possible active so that many dislocations do not move along the same slip plane. In this sense, tempered martensite crystals have more random crystal orientation per volume than ferrite crystals, and have many boundaries such as grain boundaries in an amorphous state, which is advantageous in reducing the decrease in elongation in hydrogen. Therefore, it is better to have as little ferrite as possible. On the other hand, in the martensitic stainless steel for high-pressure hydrogen parts of the present application, the ferrite amount tends to increase when the Cr content is at least 17.00% from the viewpoint of corrosion resistance, so the ferrite amount is restricted by actively introducing formula 1 and setting the lower limit to more than 0.

[0034] It is also possible to narrowly control the amount of Cr and Ni added without using formula 1 to obtain the appropriate amount of ferrite, but the composition range becomes too narrow, making manufacturing difficult. Furthermore, in the refining of stainless steel, Ni, which is an expensive additive element, is a component that cannot be removed. In addition, during the reduction refining stage, when the amount of Cr, which is a relatively inexpensive additive element, is determined by controlling the composition of the steel, there is no way to reduce the concentration other than diluting it. Therefore, in the refining of steel, it is necessary to control the amount of Cr so that it does not become too high while watching the actual value of expensive Ni, so using formula 1 is also useful from the perspective of steel refining.

[0035] In addition, since residual γ (austenite) may induce processing-induced martensite during use and cause a decrease in ductility, it is preferable to suppress it as much as possible. The suppression of this residual γ can be achieved by setting upper limits for various elements including Ni and setting the upper limit of the above formula 1 to less than 3.0, thereby obtaining a structure containing ferrite (for example, 5% or more in area ratio).

[0036] Next, the stainless steel of the present application preferably has an absorbed energy of 70 J or more obtained by a V-notch Charpy test under low-temperature conditions at a temperature of -40 ° C. In addition to the environmental temperature, high-pressure hydrogen parts are exposed to low temperatures due to the effects of pre-cooling and temperature drops due to the expansion of hydrogen gas when a large amount of high-pressure hydrogen gas is consumed in a short period of time. Therefore, low low-temperature toughness of steel is undesirable from a safety perspective. In the standard KHKS0220 (2020) for ultra-high pressure gas equipment, the toughness that high-pressure hydrogen equipment should satisfy is required to test three test pieces at the minimum design metal temperature using a V-notch Charpy impact test with a thickness of 10 mm and a V-notch depth of 2 mm, and to have an absorbed energy of 21 J or more for each test piece and an average absorbed energy of 27 J or more for the three pieces. Of course, this requirement should be met, but in order to ensure the same level as conventional austenitic stainless steels, it was decided that an absorbed energy of 70 J or more is an essential characteristic. This can further improve the reliability of high-pressure hydrogen parts.

[0037] Next, the stainless steel of the present invention preferably has mechanical properties such as a tensile strength of 700 MPa or more, a 0.2% yield strength of 500 MPa or more, and a hardness of 230 HV to 300 HV at room temperature in air.

[0038] In the pressure test of the high-pressure hydrogen parts made of the stainless steel of the present invention, a gas pressure exceeding the design pressure is applied, and it is necessary to prevent plastic deformation of the parts during the pressure test, which may impair the original functions of the parts before use, and therefore high yield strength is desirable. In addition, high tensile strength is preferable for lightweight design of parts. For these reasons, the tensile strength in air at room temperature is preferably 700 MPa or more, and the 0.2% yield strength is preferably 500 MPa or more. On the other hand, although there is no need to specify the upper limits of the tensile strength and the 0.2% yield strength, it is preferable to limit them to 1000 MPa or less because machining of the parts becomes difficult if the tensile strength is too high, and in this case, the 0.2% yield strength is also limited to a value lower than that value.

[0039] The hardness is measured using a Vickers hardness tester. The hardness at room temperature in the atmosphere is set to 230 HV or more to prevent scratches caused by cutting chips and the like during machining of the sealing surface of the high-pressure hydrogen parts, but is preferably set to 300 HV or less because if the hardness is too high, it becomes difficult to machine the fine holes that are common in high-pressure hydrogen parts.

[0040] Next, it is preferable that the mechanical properties of the stainless steel of the present invention do not decrease in a high-pressure hydrogen environment. In other words, if the 0.2% proof stress and tensile strength in a high-pressure hydrogen environment decrease compared to the 0.2% proof stress and tensile strength in air, the strength of the steel in air cannot be utilized in high-pressure hydrogen, and the mechanical design and quality assurance of parts become extremely difficult. It is also generally known that the effect of high-pressure hydrogen on the mechanical properties of steel is particularly significant at low temperatures. Therefore, it is preferable that the tensile strength and 0.2% proof stress do not decrease significantly in a high-pressure hydrogen environment at low temperatures compared to air.

[0041] Specifically, in comparing the tensile strength A1 and 0.2% yield strength A2 in a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa with the tensile strength B1 and 0.2% yield strength B2 in a low-temperature nitrogen environment at a temperature of -45°C and a pressure of 0.1 MPa, it is preferable that both A1 / B1 and A2 / B2 be 0.95 or more. By satisfying this ratio, the stainless steel of the present application is very little affected by high-pressure hydrogen, and can maintain mechanical properties almost equivalent to those under atmospheric pressure even in a high-pressure hydrogen environment.

[0042] The characteristics in a low-temperature, high-pressure hydrogen environment were represented by the characteristics in a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa. In addition, a tensile test was performed under the same conditions in a low-temperature nitrogen environment at a temperature of -45°C and a pressure of 0.1 MPa using test pieces of the same shape as above for comparison. The conditions of this low-temperature nitrogen environment were simulated in low-temperature air, and the effects of ice formation due to moisture in the air were eliminated.

[0043] Next, the stainless steel of the present application has a metal structure substantially consisting of martensite and ferrite, and the martensite preferably contains a mixture of tempered martensite and fresh martensite. Here, fresh martensite means martensite as quenched, and a martensite structure newly generated by tempering heat treatment. Moreover, a metal structure substantially consisting of martensite and ferrite means that the area ratio of the combined phase of martensite (including tempered martensite and fresh martensite) and ferrite is 95% or more.

[0044] In order to ensure the low-temperature toughness of stainless steel, it is considered to increase the mobile dislocation density. To achieve this, it is effective to minimize the amount of C added in the chemical composition and to use a martensite structure with an extremely low C content. It is also preferable to use a composition that produces a small amount of fresh martensite even after tempering.

[0045] In addition, since there is a risk of inducing deformation-induced martensite during use, it is preferable that the residual austenite is not generated as much as possible. Here, in martensitic stainless steels containing 17% or more Cr, such as the stainless steel of the present application, it is difficult to suppress the residual austenite in a metal structure with a high martensite phase ratio, so in order to suppress the residual austenite, it is preferable to have a structure containing ferrite. In other words, it is most preferable that the stainless steel of the present application contains an extremely low concentration of C, 17% or more Cr, and has a metal structure of "tempered martensite + ferrite + fresh martensite".

[0046] The area ratio of ferrite is preferably in the range of 5% to 40%. If the area ratio of ferrite is less than 5%, there is a problem that the 0.2% proof stress decreases, whereas if it exceeds 40%, there is a problem that it is difficult to maintain strength in a low-temperature, high-pressure hydrogen environment.

[0047] Next, high-pressure hydrogen parts made of the stainless steel of the present invention can be applied to parts for all applications that are used in contact with high-pressure hydrogen. In particular, the stainless steel of the present invention has very excellent corrosion resistance as a martensitic stainless steel due to the addition of Mo, so it can be used without problems even when applied to parts expected to be used in more severe corrosive environments where adhesion of sea salt particles is unavoidable, such as high-pressure hydrogen parts used on ships and the like where the usage environment is expected to be severe, and high-pressure hydrogen piping parts in cold regions exposed to salt mist containing snow-melting agents. Specific parts include, for example, piping joints, valves, pressure accumulators, safety valves, receptacles, filling nozzles, boosters, etc.

[0048] In the method of manufacturing these high-pressure hydrogen parts, at least a part made of a steel material (the present stainless steel) having the above-mentioned chemical composition is subjected to a quenching heat treatment in which it is held at a temperature of 900°C to 1020°C and then rapidly cooled, and then the part is subjected to a tempering heat treatment in which it is held at a temperature of 640°C to 770°C and then rapidly cooled.

[0049] The decrease in strength due to the decrease in ductility in a high-pressure hydrogen environment is particularly problematic at low temperatures. It is well known that in SUS304 and other stainless steels that are mainly FCC crystals, processing-induced martensite is the cause of the decrease in ductility and strength. On the other hand, in the present stainless steels, which are mainly BCC crystals and have almost no retained austenite, and even if they do exist, it is 5% or less and can be ignored, the cause of the decrease in ductility in hydrogen due to the decrease in temperature is thought to be that the lattice vibration decreases with the decrease in temperature, making it difficult for dislocation motion that switches slip planes to occur, and the movement of dislocations on specific slip planes, i.e., atomic diffusion, is concentrated.

[0050] To use BCC crystal steel in a high-pressure hydrogen environment, it is important to maintain the necessary strength while reducing the dislocation density before plastic deformation and to prevent the concentration of dislocation movement (diffusion of substitutional atoms) on specific slip planes. It is also desirable to actively utilize the crystal interfaces where the atomic arrangement that satisfies these requirements is in an amorphous state. From this perspective, it is considered desirable to use a martensite structure as the main phase, which has the characteristic of having more grain boundaries and other interfaces per volume compared to a ferritic structure.

[0051] The amount of ferrite mixed in the structure reduces the strength in a high-pressure hydrogen environment. Therefore, in the steel material defined by the above formula 1 in the above-mentioned component range, the quenching heat treatment temperature is preferably set to 900°C to 1020°C. If the quenching heat treatment temperature is less than 900°C, the steel material is easily affected by the change in the austenite / ferrite phase ratio during cooling, and there is a risk of the hardness distribution in the cross section of the part becoming non-uniform. If the quenching heat treatment temperature exceeds 1020°C, there is a risk of the strength in high-pressure hydrogen being reduced due to the excessive amount of ferrite. Therefore, the quenching heat treatment temperature is preferably set to 950°C to 1010°C.

[0052] As a method for rapidly cooling the part after it has been held in the quenching holding temperature range, water cooling, oil cooling, etc. can be adopted.

[0053] Next, after the above-mentioned quenching heat treatment, the part is subjected to a tempering heat treatment in which the part is held at a temperature of 640°C to 770°C and then rapidly cooled. By carrying out this tempering heat treatment, it is possible to obtain the desired strength and elongation in a low-temperature, high-pressure hydrogen environment, and the targeted hardness in air at room temperature.

[0054] If the holding temperature in the tempering heat treatment is less than 640°C, the hardness may become too hard due to insufficient tempering, and if it exceeds 770°C, the hardness may become too hard due to excessive fresh martensite. Therefore, the holding temperature in the tempering heat treatment after the quenching heat treatment is preferably 730 to 760°C. In this case, rapid cooling can be performed by, for example, water cooling.

[0055] Next, after the tempering heat treatment, it is preferable to further perform a re-tempering heat treatment in which the part is held at a temperature of 580°C to 650°C and then quenched. This reduces the strength difference between the hard and soft structures and increases the 0.2% yield strength. On the other hand, if the holding temperature of this second tempering heat treatment is less than 580°C, there is a risk of a defect that the hardness becomes too high due to excessive precipitates, and if it exceeds 650°C, there is a risk of a defect that the hardness becomes too high due to excessive fresh martensite. Therefore, the holding temperature in the tempering heat treatment after the quenching heat treatment is preferably 580°C to 620°C. In addition, the quenching in this case can also be performed by, for example, water cooling. EXAMPLES

[0056] Examples of the stainless steel of the present invention will now be described.

[0057] (Experimental Example 1) In this example, six types of steel were prepared, samples were made, and various evaluations were performed, as shown in Table 1. Of these, steels 1 to 3 are steels corresponding to the examples having the above-mentioned specific chemical compositions in the present application, steels 4 and 5 are comparative steels that do not contain Mo and the other compositions are within the range of the present application and are almost the same as steels 2 and 3, and steel 6 is a conventional steel equivalent to SUS305 that has been conventionally used for high-pressure hydrogen. Since steels 4 and 5 have almost the same compositions as steels 2 and 3 except for Mo, the effect of adding Mo can be accurately evaluated.

[0058] [Table 1]

[0059] <Preparation of steel material (sample)> The steel materials of Examples 1 to 3 and Comparative Examples 1 and 2 were produced by melting, then hot working to form a round bar of φ25 mm, and then heat treating each round bar under the heat treatment conditions (heat treatments 1 to 3) shown in Table 2. The steel material of Conventional Example 1 was melted, then hot working to form a round bar of φ28.7 mm, and then solution heat treatment shown in Table 2 was performed. The surface was peeled to form a round bar of φ26.5 mm, and this round bar was cold drawn to form a hexagonal column with a two-face width of 23 mm.

[0060] [Table 2]

[0061] Heat treatment 1 is the condition of quenching heat treatment (excluding conventional example 1), heat treatment 2 is the condition of tempering heat treatment after quenching heat treatment, and heat treatment 3 is the condition of re-tempering heat treatment after tempering heat treatment. The steel materials of Examples 1 and 2 and Comparative Examples 1 and 2 were produced by carrying out all of quenching heat treatment (heat treatment 1), tempering heat treatment (heat treatment 2), and re-tempering heat treatment (heat treatment 3). The steel material of Example 3 was produced by carrying out quenching heat treatment (heat treatment 1) and tempering heat treatment (heat treatment 2), without carrying out the subsequent re-tempering heat treatment. Since the steel material of Conventional Example 1 is an austenitic stainless steel equivalent to SUS305, only the normally performed solution heat treatment was carried out, and then the cold drawing process was carried out as described above. Various evaluations were carried out on the obtained steel materials.

[0062] <Microstructure Observation> From each of the steel materials after the above heat treatment, a sample was cut so that a cross section perpendicular to the length direction was exposed as the observation surface, and the observation surface was polished and then etched with Murakami's reagent. The observation surface was observed with an optical microscope, and the image obtained was analyzed to confirm the ferrite area ratio. A ferrite area ratio of 5% to 40% was evaluated as passing, and a ratio outside this range was evaluated as failing. The obtained area ratio values ​​are shown in Table 3.

[0063] <Hardness measurement> From each of the heat-treated steel materials, samples were cut out so that the cross section perpendicular to the length direction was the measurement surface, and the hardness of the measurement surface was measured using a Vickers hardness tester. A hardness of 230HV to 300HV was evaluated as passing, and a hardness outside this range was evaluated as failing. The obtained hardness values ​​are shown in Table 3.

[0064] <Tensile test in air> The tensile strength and 0.2% yield strength in air at room temperature were determined by taking JIS14A test pieces with a parallel section diameter of φ8 mm from each steel material, conforming to JIS Z2241 (Method of tensile testing of metallic materials, 2011), with the length of the steel material being the length of the test piece, and using these to perform tensile tests. The tensile strength in air at room temperature was evaluated as passing when it was 700 MPa or more, and failing when it was less than 700 MPa. The 0.2% yield strength in air at room temperature was evaluated as passing when it was 500 MPa or more, and failing when it was less than 500 MPa. The values ​​obtained are shown in Table 3.

[0065] <Tensile tests in low-temperature, high-pressure hydrogen and low-temperature nitrogen environments> For the tensile tests in a low-temperature, high-pressure hydrogen environment, tensile test pieces with a parallel section diameter of φ6 mm and a parallel section length of 30 mm were taken from each steel material so that the length direction of the steel material was the length direction of the test piece. The tensile tests were then carried out at a slow stroke speed of 0.0015 mm / sec in a device that could realize a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa. Such tensile tests at a slow strain rate are called SSRT (Slow Strain Rate Testing).

[0066] The tensile test in the low-temperature nitrogen environment was carried out in the same manner as in the low-temperature, high-pressure hydrogen environment, except that the atmospheric conditions were changed to a low-temperature nitrogen environment with a temperature of -45°C and a pressure of 0.1 MPa.

[0067] In comparing the tensile strength A1 and 0.2% yield strength A2 in a low-temperature, high-pressure hydrogen environment with the tensile strength B1 and 0.2% yield strength B2 in a low-temperature, nitrogen environment, the specimens were evaluated as passing (○) when both A1 / B1 and A2 / B2 were 0.95 or more. A1 / B1 is called the relative tensile strength (RTS), and A2 / B2 is called the relative yield strength (RYS).

[0068] <Low temperature Charpy test> For the low-temperature Charpy test, a V-notch test piece with a thickness of 10 mm and a V-notch depth of 2 mm was taken from each steel material, as specified in JIS Z2242 (2018, Charpy impact test method for metallic materials), and this was used to carry out the test in an air atmosphere at -40°C. A test with an absorbed energy of 70 J or more was evaluated as passing (○).

[0069] <Corrosion test> The specimens for the corrosion test (except for Conventional Example 1) were prepared by melting, forging, and machining to prepare rectangular specimens. After the heat treatment, rectangular specimens measuring 40 x 65 x 20 were cut out, and the cut surface was used as the evaluation surface. For Conventional Example 1, the hexagonal column specimens after the cold drawing were cut at the center in the longitudinal direction, and the cut surface was used as the evaluation surface. For the corrosion test, a composite environment corrosion test was conducted in which the specimen was repeatedly placed in a "salt spray atmosphere", a "dry atmosphere", and a "humid atmosphere". In the "salt spray atmosphere", a 5% NaCl aqueous solution was sprayed on the specimen for 2 hours in a 35°C environment. In the "dry atmosphere", hot air with a temperature of 60°C and a humidity of 20 to 30% was applied to the specimen for 4 hours. In the "humid atmosphere", the specimen was placed in an atmosphere with a temperature of 50°C and a humidity of 95 to 100%. This "salt spray atmosphere" → "dry atmosphere" → "humid atmosphere" was considered as one cycle, and 45 cycles were performed.

[0070] The rust on the evaluation surface of the test sample after the test was observed, and the evaluation was based on the rust occurrence area ratio. A rust occurrence area ratio of 0.1% or less was rated as excellent (◎), and a rust occurrence area ratio of over 0.1% was rated as excellent (◎). The value of 0.4% or less was rated as good (◯).

[0071] <Stress corrosion cracking test> The martensitic stainless steel in the present application is used after adjusting the strength by heat treatment. Therefore, in order to confirm whether the steel of the present invention in a state in which the strength has been adjusted by heat treatment has a satisfactory performance in terms of stress corrosion cracking resistance, a confirmation experiment was carried out for that purpose. Specifically, the samples used in the stress corrosion cracking test for Examples 1 to 3 and Comparative Examples 1 and 2 were prepared by subjecting each steel material to the heat treatment shown in Table 2, and then machining the steel to have a hexagonal cross section with a two-face width of 23 mm and a length of 20 mm, which is the same shape as that of the conventional example 1.

[0072] The stress corrosion cracking test was performed by immersing each sample in a boiling magnesium chloride aqueous solution, the concentration of which was adjusted so that the boiling point was 143±1°C, for 48 hours, and then visually observing the sample after removal. Samples that showed no visible cracks were evaluated as passing (○).

[0073] The evaluation results are shown in Table 3.

[0074] [Table 3]

[0075] As shown in Tables 1 to 3, each of Examples 1 to 3 has an appropriate chemical composition, satisfies formula 1, and has excellent properties that pass all evaluation items such as hardness, ferrite phase area ratio, tensile properties in a high-pressure hydrogen environment, and low-temperature impact value, and it was found that it is possible to overcome technical issues in application to high-pressure hydrogen parts and in reducing the cost thereof. In addition, the results of the corrosion test showed extremely high corrosion resistance due to the effect of adding Mo. Although it cannot be said that the corrosion resistance of the steel of the present invention is strictly equivalent to that of austenitic stainless steel, at least the results of the corrosion test this time showed evaluation results showing excellent corrosion resistance equivalent to that of austenitic stainless steel equivalent to SUS305, which is Conventional Example 1.

[0076] Comparative Examples 1 and 2 are the steels described in the above-mentioned prior application to which Mo was not added, and are described in order to understand the effect of adding Mo to the stainless steel of the present application. As shown in Table 3, Comparative Examples 1 and 2 also have excellent corrosion resistance, but it can be seen that the stainless steel of the present application has even better corrosion resistance due to the addition of Mo.

Claims

1. In mass percent, C: 0.01-0.05%, Si: 0.70% or less, Mn: 1.10% or less, P: 0.040% or less, S: 0.030% or less, Ni: 4.00-5.70%, Cr: 17.00-20.50%, Mo: 0.20 to 2.00%; Optional elements include Ca: 0.0005 to 0.0030%; As an optional element, B: 0.0005 to 0.0050% is included, The following formula 1 is satisfied: Formula 1: 3.0>Ni-0.8Cr+11.36>0, (Note that the element symbols in formula 1 represent the content (%) of each element.) A martensitic stainless steel for high-pressure hydrogen components, the balance of which consists of Fe and unavoidable impurities.

2. The absorbed energy obtained by a V-notch Charpy test with a thickness of 10 mm and a V-notch depth of 2 mm as described in JIS Z2242 (2018, Charpy impact test method for metallic materials) under low temperature conditions of -40 ° C is 70 J or more, 2. The martensitic stainless steel for high-pressure hydrogen parts according to claim 1, which has a tensile strength of 700 MPa or more, a 0.2% yield strength of 500 MPa or more, and a hardness of 230 HV to 300 HV at room temperature in air.

3. 2. The martensitic stainless steel for high-pressure hydrogen parts according to claim 1, wherein in a tensile test in which a tensile test piece having a parallel portion diameter of φ6 mm and a parallel portion length of 30 mm is pulled at a stroke speed of 0.0015 mm / sec, a comparison of tensile strength A1 and 0.2% yield strength A2 in a low-temperature, high-pressure hydrogen environment at a temperature of -45°C and a pressure of 90 MPa with tensile strength B1 and 0.2% yield strength B2 in a low-temperature nitrogen environment at a temperature of -45°C and a pressure of 0.1 MPa shows that both A1 / B1 and A2 / B2 are 0.95 or more.

4. 2. The martensitic stainless steel for high-pressure hydrogen parts according to claim 1, having a metal structure substantially consisting of martensite and ferrite, the martensite being a mixture of tempered martensite and fresh martensite, and the area ratio of the ferrite being in the range of 5% to 40%.

5. A high-pressure hydrogen part made of the martensitic stainless steel for high-pressure hydrogen parts according to any one of claims 1 to 4.

6. A method for producing a high-pressure hydrogen part using the martensitic stainless steel for high-pressure hydrogen parts according to any one of claims 1 to 4, comprising the steps of: A part made of a steel material having the above-mentioned chemical composition is subjected to a quenching heat treatment in which the part is held at a temperature of 900°C to 1020°C and then rapidly cooled; The method for manufacturing high-pressure hydrogen parts further comprises subjecting the parts to a tempering heat treatment in which the parts are held at a temperature of 640°C to 770°C and then rapidly cooled.

7. 7. The method for producing a high-pressure hydrogen component according to claim 6, further comprising the step of: after the tempering heat treatment, further subjecting the component to a re-tempering heat treatment in which the component is held at a temperature of 580° C. to 650° C. and then quenched.

Citation Information

Patent Citations

  • Low alloy steel for hydrogen accumulator, and hydrogen accumulator

    JP2018188716A